The risks of loan users for the mental health of the middle class - Muqsith, Iqbal Abdul; Puspita, Sinta; Wulandari, Merry; Putri, Amelia; Putri, Gina Malia (Priviet Social Sciences Journal, 2026)
The phenomenon of online loans (commonly known as pinjol) in Indonesia has grown rapidly in line with the advancement of digital technology. Easy access, fast disbursement processes, and the promotion of low interest rates have made pinjol highly attractive to the public, especially among the middle-class. However, behind this convenience lie various serious problems that affect users’ mental health. This study aims to analyze the risks of pinjol usage on the mental health of the middle-class community, particularly in the Parung Panjang and Tenjo Districts of Bogor Regency. The research method employed a qualitative approach supported by quantitative data. The findings show that the middle class is vulnerable to pinjol entrapment, even though they are generally considered to have better access to formal financial institutions. From a theoretical perspective, this research offers novelty by applying Lazarus and Folkman’s (1984) stress theory to the phenomenon of digital finance, thereby enriching perspectives on how primary and secondary appraisals and coping strategies shape the psychological pressure caused by pinjol. Field findings that highlight the dominance of emotion-focused coping strategies (resignation, anxiety, and avoidance) provide new contributions to the literature, as they reveal that the burden of pinjol not only creates economic problems but also reinforces a recurring cycle of stress without any long-term solutions. Therefore, stronger financial literacy, psychological support, and strict government regulations are urgently needed to prevent the harmful impacts of pinjol on Indonesia’s middle-class society.